KERJASAMA INDONESIA DAN MALAYSIA DALAM PENGGUNAAN MATA UANG LOKAL - ,, Sabrun; Pahlawan, Indra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
The use of local currency is the settlement of bilateral transactions between two countries carried out in the currency of each country, the transactions are carried out in the territory of each country. The implementation of the Local Currency Use cooperation has been carried out since 2018 with Malaysia and Thailand. In August 2020 this cooperation was implemented with Japan. Then on September 6, 2021. This study aims to analyze the purpose of Indonesia in carrying out cooperation on the Use of Local Currency with Malaysia. In this study, the researcher uses the theory of Monetary Power and the perspective of Liberalism with a nation-state level of analysis. This study uses a qualitative research method and the data obtained are primary data obtained from documents on the official websites of Bank Indonesia and the Ministry of Trade of the Republic of Indonesia as well as secondary data obtained from books, journals and scientific articles, websites, and publications. The results of this study indicate that the reason for Indonesia's cooperation in the Use of Local Currency with Malaysia is that Malaysia is a trading and investment partner for Indonesia, Indonesia's desire to expand the rupiah, and to reduce dependence on the US dollar, based on the Vision of the Money Market Development Blueprint (BPPU) 2025 Keywords: Local Currency Settlement. Dollarization. Liberalism.